If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(y + 2) = 3(2y + 3) Reorder the terms: 9(2 + y) = 3(2y + 3) (2 * 9 + y * 9) = 3(2y + 3) (18 + 9y) = 3(2y + 3) Reorder the terms: 18 + 9y = 3(3 + 2y) 18 + 9y = (3 * 3 + 2y * 3) 18 + 9y = (9 + 6y) Solving 18 + 9y = 9 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 18 + 9y + -6y = 9 + 6y + -6y Combine like terms: 9y + -6y = 3y 18 + 3y = 9 + 6y + -6y Combine like terms: 6y + -6y = 0 18 + 3y = 9 + 0 18 + 3y = 9 Add '-18' to each side of the equation. 18 + -18 + 3y = 9 + -18 Combine like terms: 18 + -18 = 0 0 + 3y = 9 + -18 3y = 9 + -18 Combine like terms: 9 + -18 = -9 3y = -9 Divide each side by '3'. y = -3 Simplifying y = -3
| 11x-(6x-4)=44 | | 6y+15x=12 | | 11x(6x-4)=44 | | x^2+xy=30 | | x^2-15x-12=0 | | 2n=4+20 | | -(x-1)x-9(x-1)=0 | | -2n+11=5 | | 3n-7=20 | | 8(w-3)=4(3-w) | | X^3-24x=0 | | -2/3t+2-3/4t=-4 | | 2/5x=3/4 | | a^2+50=0 | | q+7-2(q-2)=3(2q+1)+5q | | 1/2x+5+1/3x-5 | | 2a-10=2 | | 13n=42-3 | | 7x+6=9x | | 3x/x-5-5/x-2 | | 13x+195=13(3x+15) | | 4/3z-7+2/3z=-1 | | 88-5x=2x+11 | | -6/x-5-8/x+7 | | 15X+3-7X+4-8X=0 | | 144x^3-258x^2+105x=0 | | pi=3.1416 | | 2x+6/4+5x-2/8 | | 1/2t=-13 | | 7(x-1)=2(2x+4) | | 4x+z=19 | | X+3.5=8.8 |